Is there any geometrical golden ratio in traditional Iranian courtyard houses? - Nabavi, F.; Yahaya, A. (ArchNet, 2016)
The traditional architecture of Iran always places heavy emphasis upon beauty and harmony. This architecture is renowned for detectable principles such as modular design, geometry and specific systems of proportion. This paper involves analyzing these principles, especially geometrical golden ratio embedded within traditional houses, to confirm whether or not they are a perfect match with for the proportion system and modular design used. Eighty traditional courtyard houses in Iran were selected as a case study. The research employs the qualitative method involving archival documents, direct observation, on-site documentation and design analysis. This paper presents a detailed analysis of both proportioning and geometrical principles utilized in the facades of traditional houses and courtyards and their respective roles in creating harmony and beauty. This article concludes that despite the fact that public traditional buildings were made based on geometry and a proportioning system, this is not the case for courtyard houses. The vital factors in this case are the repetitive scale and module of openings in most traditional houses being crucial to the creation of harmony and beauty.